Evaluation of a medical education policy with compulsory rural service in China - Dan Hu; Baisong Zhang; Mingyu Huang; Min Liu; Xiulong Xia; Yanli Zuo; Xiaoyun Liu (Frontiers in Public Health, 2023)
BackgroundSince 2010, China has implemented a national programme to train general practitioners for rural areas. The programme enrolled medical students with a rural background who signed a contract for 6 years' compulsory rural service after graduation. China is transitioning its national COVID-19 strategies in view of the features of coronavirus Omicron variant, the vaccination coverage, and the need for socioeconomic development. Strengthening primary health care, especially the health workforce in rural areas, should be an important consideration during the policy transition. This study aims to evaluate the implementation process of enrolling medical students in the programme, their willingness to work in the rural settings and their actual job choice after graduation.MethodsThe study chose four medical universities in central and western China. A total of 2,041 medical graduates who have signed a contract for compulsory rural service and 1,576 medical graduates enrolled “as usual” (no compulsory rural service) were recruited in five campaigns–every June from 2015 to 2019. A survey was conducted 1 week before their graduation ceremony.ResultsThe top three reasons for choosing this programme were: a recommendation of a family member or teacher, a guaranteed job after graduation and the waiver of the tuition fee. 23.0–29.7% of the study participants were not familiar with the policy details. 39.1% of the medical students signed a contract with a county other than that of their hometown. Medical graduates on the compulsory rural service programme had very low willingness (1.9%) to work in rural areas but 86.1% of them actually worked at township health centers. In contrast, the willingness to work at township health centers was 0.2% for the comparison group (medical graduates without the contract), and their actual job choice at township health centers was 0%.ConclusionsAlthough the well-trained medical graduates on the compulsory rural service programme have low willingness to work in the township health centers, 86.1% of them choose to do so following their contract. This programme will strengthen the primary health workforce to deal with the increasing disease burden as China is transitioning its national COVID-19 strategies.